A whole-brain voxel-based analysis of structural abnormalities in PTSD: An ENIGMA-PGC study - Cheryl R.Z. See; Shuqing Si; C. Lexi Baird; Courtney C. Haswell; Ahmed Hussain; Miranda Olff; Dick J. Veltman; Jessie L. Frijling; Mirjam van Zuiden; Saskia B.J. Koch; Laura Nawijn; Li Wang; et al. (European Psychiatry, 2025)
Abstract